2013
DOI: 10.1177/1538574413493679
|View full text |Cite
|
Sign up to set email alerts
|

Low Hemoglobin Concentration Is Associated With Poor Outcome After Peripheral Arterial Surgery

Abstract: In peripheral arterial surgery, preoperative low Hb is associated with MACE and death. Further investigation is necessary to elucidate whether this relationship is causal. Meanwhile, consideration should be given to treating preoperative anemia as a significant risk factor for adverse outcome in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 39 publications
3
12
0
Order By: Relevance
“…This finding is consistent with recent literature that has shown that, in diabetic patients with PVD, Hb decline correlates with both clinical symptom deterioration and disease progression [24]. Furthermore, in diabetic patients undergoing open-bypass surgery for PVD, preoperative low Hb is associated with major cardiac events and death [25]. Further study is required to establish causal relationships.…”
Section: Discussionsupporting
confidence: 91%
“…This finding is consistent with recent literature that has shown that, in diabetic patients with PVD, Hb decline correlates with both clinical symptom deterioration and disease progression [24]. Furthermore, in diabetic patients undergoing open-bypass surgery for PVD, preoperative low Hb is associated with major cardiac events and death [25]. Further study is required to establish causal relationships.…”
Section: Discussionsupporting
confidence: 91%
“…Characteristics of the included studies are summarized in Table . A total of 949 445 patients were included, and all 24 studies reported the primary outcome of 30‐day or in‐hospital mortality.…”
Section: Resultsmentioning
confidence: 99%
“…However, stroke and myocardial infarction were reported as an outcome only in studies of patients undergoing cardiac surgery ( Table ). A haemoglobin definition was used in 17 studies, a haematocrit definition in six studies, and both definitions were used in one study. Definitions of anaemia ranged from a haemoglobin concentration of 11 to 12 g/dl or a haematocrit of 30–39 per cent for female patients, and from 11 to 14 g/dl or 30–39 per cent respectively for male patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations